Association Between Periodontitis and Cognitive Impairment in Adults: A Systematic Review - Nascimento, Priscila Cunha; Castro, Micaele Maria Lopes; Magno, Marcela Baraúna; Almeida, Anna Paula Costa Ponte Sousa Carvalho; Fagundes, Nathália Carolina Fernandes; Maia, Lucianne Cople; Lima, Rafael Rodrigues (Frontiers in Neurology, 2019)
Periodontitis is an oral inflammatory disease and may contribute to a low-grade systemic inflammation. Based on the contribution of periodontitis to systemic inflammation and the potential role of systemic inflammation in neuroinflammation, many epidemiological studies investigated a possible association between periodontitis and mild cognitive impairment or dementia. The purpose of this study was to evaluate the clinical/epidemiological evidences about the association between periodontitis and cognitive decline in adult patients. For this, a search conducted between September and October 2018 was performed of the electronic databases PubMed, Scopus, Web of Science, The Cochrane Library, LILACS, OpenGrey and Google Scholar, with no publication date or language restrictions. Analytical observational studies in adults (P – Participants), with (E – Exposure) and without periodontitis (C – Comparison) were included in order to determine the association between periodontitis and cognitive decline (O – Outcome). The search identified 509 references, of which eight observational studies were accorded with the eligibility criteria and evaluated. The results should, however, be interpreted cautiously due to the limited number of studies. This systematic review points to the need for further well-designed studies, such as longitudinal observational studies with control of modifiable variables, as diagnostic criteria and time since diagnosis of periodontitis and cognitive impairment, to confirm the proposed association.